Knowing where organic markets move next: An analysis of developing countries in the pineapple market - Linda Kleemann (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
As consumers' demand for organic products grows, selling organic products potentially opens up profitable market participation options for farmers in developing countries. This paper studies two aspects of profitability for the producers. It uses hedonic demand theory and empirical analysis to examine the relation between conventional and organic markets using the strongly growing pineapple market as an example. The analysis confirms a nonlinear dependence of the organic market on the conventional one and a non-declining premium. The author concludes that there is a larger potential of the organic market and hence the number of farmers in developing countries who can potentially benefit from growing organic products.
Keywords: L11; O13; Q13; Q17; 330; Price transmission; private voluntary standards; organic market; STAR model; TAR model